Department of philosophy in the conditions of academic capitalism approach - E. N. Ivakhnenko (Высшее образование в России)
The article considers the demolition of the university education in the sphere of the humanities in Russia of the 2000s. Against this background a more specific problem is suggested for conceptualization. The author calls it a «withstanding» of the department of philosophy inthe conditions of the market imperatives dominance. The author attempts to convey the ideathat a contemporary department of philosophy must develop its intellectual communicative resource towards the organization of its own educational activity. The teaching scene is chosen as the central position in the line of argument. There are three parties in this scene, initially endowed with asymmetric obligations – the professor, the administrator, and the student. In the author’s opinion we should not count on the establishing of any synthesis of the transmittedknowledge (the professor), market requirements (the administrator) and the demands forcompetitive advantages (the student). Any department of philosophy has to be prepared for the fact that the obligations of the three participating parties will always remain problematic and demand a «fine tuning» – i.e. a non-stop problematization and reproblematization, interpretation and reinterpretation.